Determinants of Internet Reporting by Chinese Listed Companies - TAN, Pearl Hock Neo (Institutional Knowledge at Singapore Management University, 2004)
The paper examines the extent of investor information posted on Chinese corporate websites and whether variation in the extent of information among companies can be explained by the unique institutional features of Chinese corporations as well as determinants established in the voluntary disclosure literature.